Creating smiles: a case study on the transformational power of dental CAD/CAM technology - Zeina Darwich; Atef Darwich; Marwan Al-Raeei; Chadi Azmeh (Open Exploration Publishing Inc., 2024)
The integration of digital technologies like CAD/CAM systems and intraoral scanners is transforming the field of dentistry, providing numerous benefits for both patients and dental professionals. This case study explores the significance and benefits of dental CAD/CAM technology in revolutionizing the dental industry, focusing on the creation of personalized dental restorations with precision and speed. The study emphasizes the applications of CAD/CAM technology and showcases the state-of-the-art Medit i700 intraoral scanner for detailed dental impression scanning. By adopting these advanced technologies, dental practices can save time, enhance patient satisfaction, and reduce costs in the long run. The methodology involved systematic digital assessments, planning, and execution to address cosmetic concerns, resulting in a successful transformation of a patient's smile using e.max® CAD/CAM technology and Medit i700 scanner. The case study highlights the importance of patient preference, efficiency, and accuracy in digital dentistry, demonstrating the potential for providing personalized and effective solutions for aesthetic dental concerns. Embracing digital advancements and patient-centered care is crucial for delivering high-quality and innovative solutions in modern aesthetic dentistry.